Extracorporeal cardiopulmonary resuscitation with low pump flow for blocked modified Blalock–Taussig shunt followed by spontaneous recanalization. (April 2021) - Bakos, Matija; Dilber, Daniel; Belina, Drazen; Rubic, Filip; Matic, Toni
A 2-week-old male newborn with a double inlet left ventricle developed a cardiac arrest following modified Blalock–Taussig anastomosis in pediatric intensive care unit. Probable causes of the arrest were hemodynamic instability and thrombosed shunt, which was later recanalized on extracorporeal membrane oxygenation therapy, which was successfully used with a pump flow lower than recommended in these patients—without the shunt clip, but without any complications.